2016
DOI: 10.1007/s10668-016-9827-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the hunting of mammals using local ecological knowledge: an example from the Brazilian semiarid region

Abstract: The hunting of wild animals remains a common activity in various parts of the world, especially in rural communities with poor socioeconomic conditions. To investigate patterns of mammal hunting, this study adopted a rural community located in semiarid Brazil as a model to test whether variables such as perceived abundance, activity period (day or night) and animal biomass could influence the consumption potential of mammal taxa. For this study, a checklist/interview technique using 32 photographs of mammals r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 45 publications
2
12
0
4
Order By: Relevance
“…Several reasons influence the preference and consumption of game meat, for example, economic factors (Morsello et al, 2015), ethnic and cultural identity, practices of traditional medicine (Alves et al, 2010), meat flavor, and hunting techniques (Silva Neto et al, 2017). However, hunting is an activity that affects fauna, even when it is carried out at a small scale (Machado et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Several reasons influence the preference and consumption of game meat, for example, economic factors (Morsello et al, 2015), ethnic and cultural identity, practices of traditional medicine (Alves et al, 2010), meat flavor, and hunting techniques (Silva Neto et al, 2017). However, hunting is an activity that affects fauna, even when it is carried out at a small scale (Machado et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies [40, 4850] have shown that when there is a lack of preferred species, hunters have to capture a higher number of prey of less appreciated species, as well as to increase the invested time and cover a larger area to capture the animals. It is noteworthy that several cultural factors (taboos involving the choice of species and/or hunting areas, and forms of use) are involved in the selection, capture, and use of species by local populations and have considerable impacts on the populations of the species used [4143, 48, 51]. In this sense, the understanding of these factors is essential to subsidize actions aimed at the management and conservation of the animals used [41, 43, 52].…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that several cultural factors (taboos involving the choice of species and/or hunting areas, and forms of use) are involved in the selection, capture, and use of species by local populations and have considerable impacts on the populations of the species used [4143, 48, 51]. In this sense, the understanding of these factors is essential to subsidize actions aimed at the management and conservation of the animals used [41, 43, 52].…”
Section: Introductionmentioning
confidence: 99%
“…Varios estudios (Franzen y Eaves, 2007;Lu, 2010;Mena-Valenzuela et al, 1997;Mena y Cueva, 2001;Urgilés, 2006;Vickers, 1989;Zapata-Ríos, Suárez, Utreras y Vargas, 2006;Zapata Ríos, Toasa, Neill y Jørgenson, 2004;Da Silva Neto et al, 2017) han evaluado la subsistencia de cacería (oferta y la demanda de animales).…”
Section: Introductionunclassified